2011
DOI: 10.1007/s10554-011-9814-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced exposure using asymmetric cone beam processing for wide area detector cardiac CT

Abstract: The purpose of this study was to estimate dose reduction after implementation of asymmetrical cone beam processing using exposure differences measured in a water phantom and a small cohort of clinical coronary CTA patients. Two separate 320 × 0.5 mm detector row scans of a water phantom used identical cardiac acquisition parameters before and after software modifications from symmetric to asymmetric cone beam acquisition and processing. Exposure was measured at the phantom surface with Optically Stimulated Lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Dose reduction in cardiac CT [21, 22] using iterative reconstruction methods have been extensively investigated [9, 1113, 17, 18, 30]. One group of studies compares metrics of image quality (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose reduction in cardiac CT [21, 22] using iterative reconstruction methods have been extensively investigated [9, 1113, 17, 18, 30]. One group of studies compares metrics of image quality (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were imaged with axial 320 × 0.5 mm detector row CT [20, 21] (AquilionONE, Toshiba Medical Systems Corporation, Japan) using asymmetric cone beam reconstruction [22]. All scanning was done within 1 heart beat using prospective ECG gating except for one subject who underwent 2-beat retrospective ECG-gated CCTA for an evaluation of cardiomyopathy.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging using the 320‐detector row CT paralleled the 64‐detector row CT protocol, with the following differences: the first‐generation 320×0.5‐mm scanner (Aquilion ONE, Toshiba Medical Systems Corporation) operated on the v4.51 software platform; and the craniocaudual field of view was tailored to the smallest exposure (10, 12, 12.8, 14, or 16 cm) that encompassed the heart. The default tube voltage was 120 kV.…”
Section: Methodsmentioning
confidence: 99%
“…Steigner et al in their early study reported that narrowing the phase window to 10% in prospectively ECG-triggered 320-slice CCTA resulted in low radiation dose of 5.3 mSv while still achieving diagnostic images in more than 95% of patients [33]. For a 10% phase window width, more than 20% dose reduction was achieved with use of the asymmetric approach when compared to the standard symmetric approach (4.05 mSv vs 5.33 mSv) as shown in a recent study conducted by Bedayat et al [34]. Tung et al based on their single centre experience concluded that up to 80% reduction in median radiation dose in CCTA down to 2.18 mSv from the initial installation to the most recent experience of using 320-slice CT using different approaches comprising narrowing phase window width, minimising scan length, application of advanced tube current modulation and advanced image reconstruction algorithms [35].…”
Section: Discussionmentioning
confidence: 70%